Pembelajaran Menggairahkan Dengan Ice Breaking - Luthfi, Moh. Fatih (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2014)
The duration ability of human concentration is limited to the age of each individual. The brain can focus for a certain period of time, then have to diffuse the focus. According to DePORTER (2000) the general formula for terms of focus is the age of the brain = the number of focus minutes. For example, the age of 12 students, the number is equal to the number of minutes their brains can focus. After 12 minutes it's time to practice the diffusion for 3-4 minutes, take a break! with ice breaking one of them.